2008
DOI: 10.1073/pnas.0708153105
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of chloroquine block of the inward rectifier Kir2.1 channel

Abstract: Although chloroquine remains an important therapeutic agent for treatment of malaria in many parts of the world, its safety margin is very narrow. Chloroquine inhibits the cardiac inward rectifier K ؉ current IK1 and can induce lethal ventricular arrhythmias. In this study, we characterized the biophysical and molecular basis of chloroquine block of Kir2.1 channels that underlie cardiac I K1. The voltage-and K ؉ -dependence of chloroquine block implied that the binding site was located within the ion-conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 37 publications
7
135
0
Order By: Relevance
“…However, to our knowledge, no specific blocker of Kir2.1 exists that may have therapeutic potential. Tamoxifen (14) and chloroquine (15,16) block Kir2.1 channels at low micromolar concentration but display prominent effects on other potassium, calcium, and sodium channels. Nevertheless, chloroquine has been shown to effectively terminate both atrial and ventricular fibrillation (16) and has been deemed to be more effective than flecainide as an antifibrillatory agent in a sheep model of stretch-induced atrial fibrillation (16,17).…”
Section: E299v Mutation Abolishes Inwardmentioning
confidence: 99%
“…However, to our knowledge, no specific blocker of Kir2.1 exists that may have therapeutic potential. Tamoxifen (14) and chloroquine (15,16) block Kir2.1 channels at low micromolar concentration but display prominent effects on other potassium, calcium, and sodium channels. Nevertheless, chloroquine has been shown to effectively terminate both atrial and ventricular fibrillation (16) and has been deemed to be more effective than flecainide as an antifibrillatory agent in a sheep model of stretch-induced atrial fibrillation (16,17).…”
Section: E299v Mutation Abolishes Inwardmentioning
confidence: 99%
“…Chloroquine has been found to inhibit the strong inward rectifier Kir2.1 channel in a voltage-dependent manner; i.e., it produces stronger inhibition of outward than inward current. An alanine scan of Kir2.1 pore lining residues identified amino acids Glu224, Phe254, Asp259, and Glu299, located in the cytoplasmic pore region, as critical regulators of sensitivity to chloroquine block (Rodríguez-Menchaca et al, 2008). In contrast, the D172N mutation in the M2 transmembrane domain, important for strong polyamine-mediated inward rectification of Kir2.1, did not affect the chloroquine pore-blocking effects (Rodrí-guez-Menchaca et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In cardiac myocytes, chloroquine inhibits I K1 , I KACh , and I KATP with a similar potency (Noujaim et al, 2010), but at negative membrane potentials the effect on I K1 is smaller than the effect on I KATP . Comparative molecular modeling and ligand docking of chloroquine in the intracellular domains of Kir2.1 suggested that chloroquine interacts with negatively charged amino acids facing the cytoplasmic pore of the channel (Rodríguez-Menchaca et al, 2008;Noujaim et al, 2010). In contrast, chloroquine was predicted to bind the Kir6.2 cytoplasmic pore in a configuration that seemed unlikely to impede potassium ion permeation (Noujaim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…African children with severe Plasmodium falciparum malaria often present with metabolic complications which include impairment of glucose homeostasis, cardiovascular and kidney functions partly ascribed to P. falciparum infection and/or drugs used manage malaria [1] .…”
Section: Introductionmentioning
confidence: 99%